The Effect of Water Quality Dynamics on The Growth Performance of Vannamei Shrimp Litopenaeus vannamei in Intensive Ponds at CV. Daun Prima, East Java - Pratiwi, Rifqah; Hariyadi, Dimas Rizky; Zahwa, M. Akhyar Defa'I; Ramadhani, Dian Eka (Sains Akuakultur Tropis : Indonesian Journal of Tropical Aquaculture, 2024)
Litopenaeus vannamei shrimp is a leading fisheries commodity in Indonesia. It’s quite popular for cultivation related to strong attributes that include; fast growth, disease resistance, and high economic value. One of the successes of shrimp cultivation is greatly influenced by water quality. Water quality dynamics describes the occurrence of fluctuations in water quality in the media, which is an important factor that influences shrimp growth performance. This study aimed to evaluate the effect of water quality dynamics on the growth performance of vannamei shrimp in intensive ponds in CV. Daun Prima, East Java. The research method used is a case study which includes interviews, observation, and following all stages of the shrimp production process at CV. Daun Prima. The results showed optimal water quality, including temperatures of 27 – 31°C, brightness of 20 – 45 cm, pH of 7.5 – 8.1, dissolved oxygen of 4.50 – 5.33 mg/L, and salinity of 30 – 33 g/L. Growth performance of the shrimp produced, such as ABW of 3.55 – 15.33 grams/ind, ADG of 0.21 – 0.35 grams/day, and survival rate of 80%. Water quality dynamics in intensive ponds are stable during maintenance. Water quality parameters are within the optimal range to support the growth performance of shrimp. This study benefits shrimp farmers, industry stakeholders, and policymakers by identifying optimal water quality conditions that enhance growth performance and survival rates in vannamei shrimp farming.Keywords:  Dynamics, Growth Performance, Litopenaeus vannamei, Shrimp, Water Quality